Beyond any Particularity: Hegel's Universalistic Rethinking of Protestant Sacramentology - Oseka, Mateusz (Silliman Journal, 2022)
This paper explores Hegel’s sacramentology within his system and in view of its determinants among which the Kantian reinterpretation of the sacraments was especially influential. The study demonstrates that the Right Hegelianism as represented by Marheineke tempered the universalistic potential of Hegel’s sacramentology in order to accommodate his legacy to the ecclesiastical prerequisite of that time. Divergent hermeneutical presuppositions of the Reformation theology and of the Hegelianism were elucidated and analysed in terms of their impact upon sacramentology.